Printed Solar Cells and Energy Storage Devices on Paper Substrates. (30th January 2019) - Brunetti, Francesca; Operamolla, Alessandra; Castro‐Hermosa, Sergio; Lucarelli, Giulia; Manca, Valerio; Farinola, Gianluca M.; Brown, Thomas M.
Abstract: Paper is a flexible material, commonly used for information storage, writing, packaging, or specialized purposes. It also has strong appeal as a substrate in the field of flexible printed electronics. Many applications, including safety, merchandising, smart labels/packing, and chemical/biomedical sensors, require an energy source to power operation. Here, progress regarding development of photovoltaic and energy storage devices on cellulosic substrates, where one or more of the main material layers are deposited via solution processing or printing, is reviewed. Paper can be used simply as the flexible substrate or, exploiting its porous fiber‐like nature, as an active film by infiltration or copreparation with electronic materials. Solar cells with efficiencies of up to 9% on opaque substrates and 13% on transparent substrates are demonstrated. Recent developments in paper‐based supercapacitors and batteries are also reviewed with maximum achieved capacity of 1350 mF cm −2 and 2000 mAh g −1, respectively. Analyzing the literature, it becomes apparent that more work needs to be carried out in continuing to improve peak performance, but especially stability and the application of printing techniques, even roll‐to‐roll processing, over large areas. Paper is not only environmentally friendly and recyclable, but also thin, flexible, lightweight, biocompatible, and inexpensive. Abstract : The progress regarding development of solar cells and energy storage devices on paper substrates, where one or more of the main material layers are deposited via solution processing or printing, is reviewed. Paper is not only environmentally friendly and recyclable, but also thin, flexible, lightweight, biocompatible, inexpensive, and appealing as a substrate in the field of flexible printed electronics.